Формула добра: [повесть] / Михаил Самарский - Самарский Михаил Александрович (Приключения необыкновенной собаки, 2017)
Экземпляры: ф.18 (20181009) / Инвентарный номер: 3000 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: С 17 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6-44